Image Processing Algorithm for Calculating Uniformity of Carbon Surface Image Heating Element - Soo Hwang, Hyung; Ho Cho, Joon (International Journal of Engineering and Technology, 2018)
Background/Objectives: In this paper, numerical calculation method using image processing technology for percentage and uniformity of carbon fibers of planar heating element was proposed.Methods/Statistical analysis: The manufacturing method of the planar heating element is made by chopping the carbon fiber in small size and bonding it again via the dispersing agent. Filter the carbon fiber solution bound using a dispersant on the next nonwoven fabric. The last step is to obtain planar carbon fibers in the form of nonwoven fabrics for drying the filtered carbon fibers.Findings: n the planar heating element, electricity may be applied to the carbon fiber on the surface produced in this manner. Calculation of the ratio and uniformity of the planar heating element in this paper addressed four sample images (0.2 wt.%, 0.4 wt.%, 0.8 wt.%, 2.4 wt.%). In this method, the image of the planar heating element was divided into 5 Ã— 5, converted into a binary image, and then the ratio and uniformity were numerically calculated.Improvements/Applications: The image analysis of the planar heating element proposed in this paper can be interpreted more accurately by combining it with the conventional method.Â Â